Evaluation of the poly herbal drug: Keelvayu Nivarana Churnam - G, Vijayabaskar; V, ELANGO (Journal of Drug Delivery and Therapeutics, 2019)
Siddha Medicine is regaining its lost glory throughout the World. For the universal acceptations of Siddha medicine we should standardize by scientific validation at various levels. Herbals have been an important source of medicine with qualities for thousands of years.  Phytochemicals are the active principles of the herbal drug. Keelvayu nivarana churnam is one of the poly herbal drugs used for Arthritis. In this study we carried out powder microscopy for identification of the ingredient medicinal plants.  We studied Physicochemical parameters like appearance, pH, total ash, loss on drying; water soluble extractive, alcohol soluble extractive, bulk density and tap density are evaluated.  In Phyotochemical screening the presence or absence of alkaloids, flavanoides, tannins, proteins, sterols, carbohydrates, glycosides, terpenoides, saponins and starch. We did Gas chromatography and Mass spectroscopy (GC-MS/MS) for the identification of bioactive compounds of Keelvayu nivarana churnam. These findings support the therapeutic value of Keelvayu nivarana churnam in Arthritis.Keywords: Arthritis; Keelvayu nivarana churnam; Powder Microscopy; Physicochemistry and Phytochemistry; Gas chromatography–mass spectrometry (GC-MS/MS).